Leguminosae do parque nacional das nascentes do rio Parnaíba, cerrado brasileiro: estudo florístico e tratamento taxonômico para o gênero Chamaecrista (L.) Moench - BASTOS, Maria da Conceição de Carvalho (2024)
This study aimed to conduct a survey of legume species in the Parque Nacional das Nascentes do Rio Parnaíba (PNNRP) and, based on this survey, provide taxonomic treatment for the most representative genus. The PNNRP, located at the confluence of the states of Bahia, Maranhão, Piauí, and Tocantins, was established as a Conservation Unit to preserve the sources of the Parnaíba River and part of the Cerrado, in a region facing significant agricultural expansion, especially soybean monoculture and extensive cattle ranching. Despite the diversity of environments in the PNNRP, studies on plant diversity are still insufficient, with the management plan being the only source of taxonomic information available so far. The species survey was conducted through five collection expeditions during the years 2022 and 2023, each lasting about a week, aiming to cover the flowering periods of as many species as possible. For specimen sampling, we used the free-walking method, covering as many physiognomies as possible. As a result, 69 species and two infraspecific taxa were cataloged, distributed across 29 genera and representing four subfamilies: Caesalpinioideae, Papilionoideae, Detarioideae, and Cercidoideae. Of these, 14 species were new records for the Northeast region or for the states covered by the park. The Caesalpinioideae subfamily stood out as the most diversified group, comprising 35 species. Chapter I of the dissertation provides a general context on the Cerrado, the MATOPIBA region (acronym formed by the initials of the states Maranhão, Tocantins, Piauí, and Bahia), and the Leguminosae studies developed in this area. Chapter II presents the general list of taxa cataloged in the study area, including photographs of live species, comments, and geographic distribution. Chapter III deals with the taxonomic treatment for the Chamaecrista genera, the most representative in the study area. This chapter includes an identification key, morphological descriptions, illustrations, data on geographic distribution, habitat, and taxon comments. The information provided in this study highlights the importance of floristic surveys in Conservation Units in the Brazilian Cerrado and contributes to a deeper understanding of Leguminosae in the PNNRP, emphasizing the park’s relevance for the preservation of Brazilian flora.